2022
DOI: 10.1371/journal.pone.0279751
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of compliance with 24-h movement guidelines among children from urban and rural Kenya—The Kenya-LINX project

Abstract: Background Like many countries in sub-Saharan Africa, Kenya has experienced rapid urbanization in recent years. Despite the distinct socioeconomic and environmental differences, few studies have examined the adherence to movement guidelines in urban and rural areas. This cross-sectional study aimed at examining compliance to the 24-hour movement guidelines and their correlates among children from urban and rural Kenya. Method Children (n = 539) aged 11.1 ± 0.8 years (52% female) were recruited from 8 urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A total of 39 studies ( 16 75 ) reported overall adherence to 24-h movement guidelines. Regarding age group, 26 studies ( 16 , 20 , 21 , 23 25 , 27 , 28 , 31 , 33 37 , 48 , 54 , 56 , 59 62 , 66 , 67 , 70 , 71 , 74 ) focused on children and 22 studies ( 20 , 22 , 26 , 28 , 30 32 , 38 , 46 , 48 , 52 , 53 , 56 58 , 62 , 64 , 66 , 69 , 72 74 ) focused on adolescents. In terms of gender, 19 studies ( 15 , 20 , 29 , 30 , 32 , 33 , 36 , 37 , 41 , 42 , 45 , 47 , 51 , 53 , 55 , 62 , 63 , 65 , 75 ) included both boys and girls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 39 studies ( 16 75 ) reported overall adherence to 24-h movement guidelines. Regarding age group, 26 studies ( 16 , 20 , 21 , 23 25 , 27 , 28 , 31 , 33 37 , 48 , 54 , 56 , 59 62 , 66 , 67 , 70 , 71 , 74 ) focused on children and 22 studies ( 20 , 22 , 26 , 28 , 30 32 , 38 , 46 , 48 , 52 , 53 , 56 58 , 62 , 64 , 66 , 69 , 72 74 ) focused on adolescents. In terms of gender, 19 studies ( 15 , 20 , 29 , 30 , 32 , 33 , 36 , 37 , 41 , 42 , 45 , 47 , 51 , 53 , 55 , 62 , 63 , 65 , 75 ) included both boys and girls.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of gender, 19 studies ( 15 , 20 , 29 , 30 , 32 , 33 , 36 , 37 , 41 , 42 , 45 , 47 , 51 , 53 , 55 , 62 , 63 , 65 , 75 ) included both boys and girls. In terms of geographical region, 18 different countries were identified, including 3 in Africa ( 16 , 25 , 54 ), 20 in Asia ( 16 , 22 , 30 , 34 , 37 , 39 , 41 , 44 , 51 53 , 55 , 56 , 58 , 59 , 62 , 70 72 , 75 ), 10 in Europe ( 16 , 26 , 42 , 48 , 50 , 60 , 62 , 63 , 68 , 70 ), 4 in Oceania ( 16 , 35 , 43 , 45 ), and 22 in North America ( 16 – 20 , 23 , 24 , 28 , 29 , 31 33 , 38 , 40 , 46 , 47 , …”
Section: Resultsmentioning
confidence: 99%
“…Similarly to other low-middle income countries, Brazil has been experiencing a rapid urbanization in recent decades, that may impact on movement behaviors levels, and that could be partially responsible for the high prevalence of Brazilian rural young children affected by overweight and obesity (Saúde, 2019). For instance, a study conducted among Kenyan middle childhood children from urban and rural areas showed that compliance with the combined movement behaviors guidelines was low overall (7%), and higher among rural (10%) than urban (5%) children (Swindell et al, 2022), supporting similar findings from Mozambican children (17.7% vs. 3.6% for rural and urban setting, respectively) (Manyanga et al, 2019). The authors suggest that urban environment characteristics, such as lack of walkability, and safety concerns may be negative linked to an active childhood (Manyanga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%